Response of durum wheat (Triticum durum Desf.) growth to salt and drought stresses - Rhouma SAYAR; Houcine BCHINI; Mohamed MOSBAHI; Habib KHEMIRA (Czech Journal of Genetics and Plant Breeding, 2010)
Two durum wheat (Triticum durum Desf.) cultivars were tested for salt and drought tolerance at germination, seedling emergence and early seedling growth in NaCl and PEG-8000 solutions of different osmotic potentials (-0.2, -0.4, -0.6 and -0.8 MPa). Daily and final germination and emergence percentage, as well as germination and seedling emergence rate, seedling growth, fresh and dry weight were recorded under controlled conditions. Results showed that germination and emergence rates were delayed by both solutions in both cultivars, but Omrabia showed higher germination and emergence rates than BD290273 in NaCl while BD290273 was less affected by NaCl and PEG solutions at the emergence stage. Sodium chloride had a lesser effect on both cultivars in terms of germination rate, emergence rate, final germination and emergence percentage than did PEG-8000. This conclusively proves that the adverse effect of PEG-8000 on germination, emergence and early seedling growth was due to the osmotic effect rather than to the specific ion. Seedling growth was reduced by both stresses. However, NaCl usually caused less damage than PEG to durum wheat seedlings, suggesting that NaCl and PEG acted through different mechanisms.